Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c7fo01790a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combined intervention with a lentil protein hydrolysate and a mixed training protocol on the lipid metabolism and hepatic markers of NAFLD in Zucker rats

Abstract: Metabolic syndrome is a cluster of metabolic alterations characterized by central obesity, dyslipidemia, elevated plasma glucose, insulin resistance (IR) and non-alcoholic fatty liver disease (NAFLD). In this study, a combined intervention of a lentil protein hydrolysate and a mixed training protocol was assessed in an animal experimental model of genetic obesity and metabolic syndrome. Thirty-two male obese and 32 lean Zucker rats were divided into eight different experimental groups. Rats performed a mixed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…However, greater protein supplementation can affect carbohydrate and fat metabolism including NAFLD. Rosario Martínez et al showed such an effect using legume (lentil) (25). The unique fatty profile in the recently developed high-oleic varieties (D7) is similar to the olive oil profile.…”
Section: Discussionmentioning
confidence: 98%
“…However, greater protein supplementation can affect carbohydrate and fat metabolism including NAFLD. Rosario Martínez et al showed such an effect using legume (lentil) (25). The unique fatty profile in the recently developed high-oleic varieties (D7) is similar to the olive oil profile.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, different extraction conditions may be implemented for this particular action on legume-derived functional products. In this sense, the protein hydrolyzates obtained after aqueous extraction at basic pH have been shown to exhibit an interesting polyphenolic profile and elevated mineral content [13,29]. Both of these are important features in the design of nutraceuticals that show strong bioactive potential and provide nutritionally essential elements at levels close to 10-15% of their Recommended Dietary Allowances with relatively low doses of the product.…”
Section: Discussionmentioning
confidence: 99%
“…High resolution mass spectrometry analysis was performed by Ultra Performance Liquid Chromatography (UPLC) coupled with a Quadrupole Time of Flight (QTOF) Mass Spectrometer (Synap G2, Waters, Milford, MA, USA) as previously reported by Martinez et al [ 29 ]. Briefly, the analytical separation of polyphenols was performed on an Acquity HSS T33 analytical column (100 mm × 2.1 mm internal diameter, 1.8 μm; Waters, Milford, MA, USA) with a mobile phase that consisted of a gradient formed by combining deionized water with 0.5% of acetic acid as solvent A, and acetonitrile with 0.5% of acetic acid as solvent B.…”
Section: Methodsmentioning
confidence: 99%
“…Several alterations in glucose and lipid metabolism have been described related to the development of metabolic syndrome in the obese Zucker rat experimental model. In this sense, we previously described impaired glucose tolerance associated with hyperinsulinemia and hyperglycemia as well as hypertriglyceridemia in these animals (19,20,32), which could lead to diabetic nephropathy. The diabetic nephropathies are described as kidney injuries associated with diabetes mellitus and affecting kidney glomerulus, arterioles, tubules, and the interstitium, including clinical signs as persistent proteinuria, from microalbuminuria progressing to albuminuria, leading to reduced glomerular filtration rate and end-stage renal disease.…”
Section: Discussionmentioning
confidence: 89%